005: APPLICATION OF BEST PRACTICES OF ON LINE INTERACTIVE LEARNING IN HEALTH HUMAN RESOURCE MANAGEMENT COURSE: A UPOU EXPERIENCE. (24th August 2015) - Oruga, Myra D
Abstract : Background: Application of best practices of on line interactive learning in Health Human Resource Management course: A UPOU Experience was explored in this study. Objectives: This qualitative study used best practices of on line interactive learning criteria to analyze the learnings of the students enrolled in Health Human Resource Management course. Methods: The students narrate their experiences in terms of behavior criterion, student-faculty interactions, use of technology and their learning environment. The respondents, age, gender, civil status, educational attainment, location and occupation were profiled. Result: Majority of them are male, married, belong to 35–45 years old, 5 of the 6 respondents were medical doctors, majority of them are in local setting. Analysis of the experiences revealed that students were challenged in answering health human resource cases given to them by the faculty-in-charge and that they are even more challenged in finishing the 180 contact hours of practicum in their preferred agency. Time was a factor since most of them were working full time. All students narrated that they have applied what they learned in their work. Conclusion: The experiences shared by the students enrolled in health human resource management will continuously evolved as the course is re-tooled and re-developed in the future. Key The experiences shared by the students enrolled in health human resource management will continuously evolved as the course is re-tooled and re-developed in the future.